Legal Aspects of Consumer Personal Data Protection in the Digital and AI Era - Asman Siagian; Anto Mutriady Lubis; Rahmadany (International Journal of Society and Law, 2025)
This study aims to analyze the legal aspects of consumer personal data protection in the context of the development of digital technology and artificial intelligence (AI). With rapid technological advances, the collection and processing of personal data are becoming increasingly complex, posing new challenges in protecting consumer privacy rights. This study uses a qualitative approach, examining existing regulations, including the Personal Data Protection Act and international standards such as the GDPR. Through an analysis of various legal cases and industry practices, this study identifies gaps in existing legal protections and provides recommendations for strengthening existing regulations. The findings indicate that despite sufficient regulations, implementation and compliance remain challenges. This study concludes that a more adaptive and comprehensive legal framework is needed to protect consumer personal data in the digital and AI era, as well as the need for consumer awareness and education regarding their rights in this context.